Understanding chronic fatigue syndrome : an introduction for patients and caregivers - Ali, Naheed, 1981- (Rowman and Littlefield, 2015)
Chronic fatigue syndrome is a confusing and disputed disorder that affects more and more people. Here, Naheed Ali sheds light on this ill-understood and yet debilitating disorder. Readers will come away with not only a better understanding of what constitutes CFS but various ways of dealing with its symptoms.